2022
DOI: 10.3390/polym14194128
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Sensitive Poly (N-isopropylacrylamide-co-polyacrylamide) Hydrogel for pH-Responsive Therapeutic Delivery

Abstract: Stimuli-response polymeric nanoparticles have emerged as a carrier system for various types of therapeutic delivery. In this study, we prepared a dual pH- and thermo-sensitive copolymer hydrogel (HG) system (PNIPAm-co-PAAm HG), using N-isopropyl acrylamide (NIPAm) and acrylamide (AAm) as comonomers. The synthesized PNIPAm-co-PAAm HG was characterized using various instrumental characterizations. Moreover, the PNIPAm-co-PAAm HG’s thermoresponsive phase transition behavior was investigated, and the results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 44 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…Moreover, for further in vivo studies, the excellent capacity of DOX is required. The DOX-loaded MNCs should be stable at a plasma pH of ~7.4 and enable efficient drug release in cancer tissue (pH of 5–5.5) [ 45 , 64 , 66 , 69 , 70 , 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for further in vivo studies, the excellent capacity of DOX is required. The DOX-loaded MNCs should be stable at a plasma pH of ~7.4 and enable efficient drug release in cancer tissue (pH of 5–5.5) [ 45 , 64 , 66 , 69 , 70 , 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the development of dual-stimuli controlled delivery systems, such as pH and temperature-responsive systems, is thought to be important for regulated and selective drug delivery in target sites. Because of their ability to respond to temperature changes in the presence of biological fluid, thermosensitive hydrogels are gaining popularity in drug delivery and tissue encapsulation [ 22 ]. Among them, thermoresponsive poly(N-isopropyl acrylamide) (PNIPAm) is the most well-investigated polymer due to its distinctive phase transition from an extended hydrophilic state to a collapsed hydrophobic state in water at around 32 °C.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, drug-loaded hydrogels have drawn considerable attention due to the possibility of modulating the local release of medicines through different mechanisms, according to the hydrogel nature. In order to achieve this goal, several types of hydrogels have been explored, such as degradable hydrogels [ 33 ], stimuli-responsive hydrogels [ 34 ], redox-responsive hydrogels [ 35 ], molecularly imprinted hydrogels [ 36 ], etc. In particular, the polyacrylamide hydrogel (PAAG) is especially interesting because it is a biocompatible [ 37 ], non-toxic, and non-degradable synthetic product [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our approach involves the use of only PAAG without the need of polymer blends [ 33 ], grafting [ 42 ], etc., as is usual in most of the studies reported in the literature. It takes advantage of a simple and well-known methodology for the synthesis of PAAG in aqueous media, without the need for special techniques such as organic solvent evaporation through rotary evaporator [ 34 ], microwave assistance [ 42 ], UV irradiation [ 43 ], etc., which makes it appropriate for mass fabrication, since its intended potential application is the coating of Ti implant surfaces. In addition, the thin, non-degradable PAAG coating also overcomes the burst release found in degradable hydrogels [ 33 ], which could result in a harmful effect (possible cytotoxicity and inflammatory response).…”
Section: Introductionmentioning
confidence: 99%